Association patterns between 2D:4D ratio and age at menarche: the impact of methodology - Eresheim, Rebecca; Schaufler, Savannah; Kirchengast, Sylvia (Anthropological Review, 2020)
The ratio of index finger to ring finger length (2D:4D) is a sexually dimorphic feature and widely used as an indicator of prenatal androgen-estrogen exposure. Several studies have investigated the relationship between the 2D:4D ratio and the onset of the first menstrual period (menarche) in women. The present study tested the association patterns between 2D:4D ratio and age at menarche. Furthermore, the impact of methods of measuring finger lengths was considered. Two samples were used to conduct the study. One sample consisted of 110 women who self-measured their finger lengths. The finger length measurements in the second sample (88 women) were taken from one trained observer using the caliper-based technique. Age at menarche was determined using a retrospective method. Women from the first sample reported an average age for the onset of the first menstrual bleeding at 12.9 (SD = 1.4) years of age. There was no significant association between the left and right 2D:4D ratio and the age at menarche. The second sample showed a mean age at menarche at 12.8 (SD = 1.3) years of age. Here, the right hand 2D:4D ratio and age at menarche were significantly correlated (p<0.001). A more feminine 2D:4D ratio was significantly associated with an earlier menarcheal age only in the sample with direct finger length measurements by a trained investigator. The sample using self-measurements yielded no significant associations between menarcheal age and 2D:4D. The use of a reliable and well-founded methodology is essential for obtaining meaningful results.